VD_FINDINFO HC / 2022 / 390 vom 13. Mai 2022 - VD Tribunal cantonal (2022)
EXPULSION DE LOCATAIRE, CAS CLAIR, DROIT D'ÊTRE ENTENDU, BAIL À LOYER | 257d CO, 86 CO, 87 CO, 29 Cst., 311 al. 1 CPC (CH), 317 al. 1 CPC (CH)